Pharmacy students' knowledge and perceptions about adverse drug reactions reporting and pharmacovigilance - Kingston Rajiah; Mari Kannan Maharajan; Shashina Nair (Elsevier, 2016)
Pharmacy students' knowledge about adverse drug reaction reporting can impact their attitude towards patient care and issues on patient safety. The aim of this study was to investigate the knowledge and perception of pharmacy students about adverse drug reaction reporting and pharmacovigilance and to study their willingness to report. A cross-sectional study using a validated questionnaire was conducted among the university students. The demographic details of the respondents were studied. The number of female respondents was comparatively higher than the male respondents. There were no significant differences by gender regarding the knowledge on adverse drug reaction reporting and pharmacovigilance except with the knowledge of post-marketing surveillance for which male students appeared to be more knowledgeable than female students. The results showed that the pharmacy students had sufficient knowledge and there are significant differences in perception among the students on adverse drug reaction reporting.